Preoperative Management of MGD with Vectored Thermal Pulsation before Cataract Surgery: A Prospective, Controlled Clinical Trial. (17th February 2021) - Zhao, Yinying; Li, Junhua; Xue, Keyun; Xie, Jialu; Xie, Gongpei; Gu, Siyi; Zhao, Yune
ABSTRACT: Purpose : To investigate the efficacy of preoperative monocular treatment in elderly cataract patients with Meibomian Gland Dysfunction (MGD) utilizing vectored thermal pulsation treatment. Materials and Methods : This study was a prospective, examiner-masked contralateral eye clinical trial. Patients previously diagnosed with MGD undergoing uncomplicated cataract surgery in two eyes were enrolled. The eye perceived by the patient to be more symptomatic of MGD received a 12 min vectored thermal pulsation treatment using the LipiFlow Thermal Pulsation System, and was referred to as the LipiFlow-surgery eye. The contralateral eye then served as the nonLipiFlow-surgery eye. Patients with MGD not undergoing cataract surgery were enrolled as the control group. Within the control group, the eye that received LipiFlow treatment was considered the LipiFlow-nonsurgery eye, while the contralateral eye served as the nonLipiFlow-nonsurgery eye. All patients were examined before treatment and at one-week, one-month, and three-month intervals after treatment. Clinical parameters included dry eye symptoms, average lipid layer thickness (LLT-ave), tear breakup time (TBUT), corneal staining, Schirmer I tests, Meibomian glands yielding liquid secretion (MGYLS), and meibomian gland dropout. Results : A total of 32 patients (64 eyes) were examined during the three-month follow-up. There was a significant reduction in dry eye symptoms in non-surgery patients with monocular treatment of MGD, while no change in surgery patients was observed. Significant improvement of MGYLS in LipiFlow-surgery and LipiFlow-nonsurgery eyes during the follow-up time ( p < .001) was reported, while no difference was observed in nonLipiFlow-surgery and nonLipiFlow-nonsurgery eyes. A statistically significant difference was seen in TBUT between LipiFlow-surgery and nonLipiFlow-surgery eyes at one-week and one-month intervals ( p = .019 and 0.019, respectively). Differences in other clinical parameters were not statistically significant. Conclusions : Our findings suggest that although subjective symptoms were not alleviated, a single application of LipiFlow treatment before cataract surgery is effective in alleviating blockage of meibomian glands and preventing the decline of TBUT after cataract surgery.